ChemInform Abstract: Synthesis of Novel 5‐(3‐Alkylquinolin‐2‐yl)‐3‐aryl Isoxazole Derivatives and Their Cytotoxic Activity. Issue 32 (12th August 2014) - Sambasiva Rao, P.; Kurumurthy, C.; Veeraswamy, B.; Poornachandra, Y.; Ganesh Kumar, C.; Narsaiah, B.
Abstract: All the final products are screened against four human cancer cell lines.